Profiling of Petroselinum sativum (mill.) fuss phytoconstituents and assessment of their biocompatibility, antioxidant, anti-aging, wound healing, and antibacterial activities - Mahdi, Ismail; Imbimbo, Paola; Annaz, Hassan; Bakrim, Widad Ben; Sahri, Nihad; Alaoui, Asmae; Monti, Daria Maria; Sobeh, Mansour (Frontiers in Nutrition, 2024)
Petroselinum sativum, known as parsley, is a fragrant herb that possesses a rich heritage of utilization in traditional medicinal practices. In this study, we annotated the phytocontents of the aqueous and ethanolic extracts of P. sativum and investigated their antioxidant, cytoprotective, antiaging, wound healing, and antibacterial activities. LC-MS/MS analysis of both extracts revealed the presence of 47 compounds belonging to diverse groups including organic acids, phenolic acids, and flavonoids. By MTT assay, the extracts were fully biocompatible on immortalized human keratinocytes (HaCaT) while they inhibited intracellular ROS formation (DCFDA assay) and prevented GSH depletion (DTNB assay) upon UVA exposure. In addition, the extracts were potent in inhibiting the in vitro activities of skinrelated enzymes mainly elastase, tyrosinase, collagenase and hyaluronidase. Using the scratch assay, P. sativum aqueous extract significantly enhanced wound closure when compared to untreated HaCaT cells. Moreover, both extracts inhibited P. aeruginosa's growth, reduced biofilm formation, and impaired the swimming and swarming motilities. Also, the aqueous extract was able to inhibit the production of bacterial pigments on plates. These findings strongly suggest the usefulness of P. sativum as a source of phytochemicals suitable for dermo-cosmeceutical applications.